PARTISIPASI PEMUDA DALAM KONSERVASI SUMBERDAYA ALAM LAUT DAN PESISIR DI DESA CIBALONG, GARUT SELATAN - Sihadi Sihadi (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2012)
The purpose of this research to determine the relationship between indigenous knowledge, attitudes toward the environment, and motivation in keeping marine environment with the participation of youth in the natural resources conservation of marine and coastal. The research was conducted at Cibalong Coastal Village, Garut Selatan, 2009. with n = 170 selected randomly.The research findings are as follow: (1) there is positive correlation between of indigenous knowledge with the participation of youth in the natural resources conservation of marine and coastal, (2) there is positive correlation between attitudes toward the environment with the participation of youth in the natural resources conservation of marine and coastal, (3) there is positive correlation between of motivation in keeping marine environment with the participation of youth in the natural resources conservation of marine and coastal, and (4) there is positive correlation between of indigenous knowledge, attitudes toward the environment, and motivation in keeping marine environment with the participation of youth in the natural resources conservation of marine and coastal.